ANALISA USER EXPERIENCE TERHADAP FITUR DI APLIKASI ZENIUS MENGGUNAKAN HEART FRAMEWORK - Agdeka Cory Zarkasi; Anita Sari Wardani; Sucipto Sucipto (Universitas Methodist Indonesia, 2022)
Learning facilities in the current digital era have developed far, including the learning institution PT.Zona Edukasi Nusantara (Zenius) which has begun to adapt by launching an application for learning facilities called Zenius. Currently Zenius has become one of the edu tech in Indonesia that has a large number of active service users. To ensure the convenience of application users, it is necessary to measure User Experience to find out whether there is still need for improvement in its use. In this study, the HEART Framework is used as a framework for measuring the Zenius application using the questionnaire method. The results of this study indicate that there needs to be some improvements in various aspects such as redesign of the display by paying attention to aspects of user comfort and interface display, feature innovation, adding features and socializing features.